1994
DOI: 10.1016/0304-3959(94)90144-9
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal guanethidine sympathectomy suppresses autotomy and prevents changes in spinal and supraspinal monoamine levels induced by peripheral deafferentation in rats

Abstract: In the rat, sciatic and saphenous nerve section resulted in self-mutilation of the ipsilateral limb. Fifteen and 60 days after surgery, monoamine levels were altered not only in the spinal cord but also in supraspinal structures. Thus, in the ipsi- and contralateral sides of the spinal lumbar region, an increase in the levels of 5-hydroxyindoleacetic acid (5-HIAA) was observed 15 days after surgery and in the levels of serotonin (5-HT) and noradrenaline 60 days later. Changes in the content of 5-HT and its met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The prevalence of depression in the general population is estimated to be 9.1% [8] , and it has a major impact on public health and global disease burden [9] . The prevalence of depression in the orthopedic population is believed to be even higher [10] , [11] , [12] , [13] . With respect to opioid use, depression has been shown to be strongly associated with chronic pain, and the prevalence of opioid use among patients with depression doubles compared with that of an appropriate control population [14] .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of depression in the general population is estimated to be 9.1% [8] , and it has a major impact on public health and global disease burden [9] . The prevalence of depression in the orthopedic population is believed to be even higher [10] , [11] , [12] , [13] . With respect to opioid use, depression has been shown to be strongly associated with chronic pain, and the prevalence of opioid use among patients with depression doubles compared with that of an appropriate control population [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover as seen above, the 5HT and 5HIAA levels increase after a peripheral nerve axotomy in the periaqueductal grey matter and in the trigeminal nucleus. However, 5HT and 5HIAA levels, decrease in ventromedial thalamus and medial prefrontal cortex in a neuropathic and in formalin test respectively [6]- [8]. This discrepancy on these results may be due to the brain region studied, the pain model used or even the technique employed for the measurement of the release of the neurotransmitter.…”
Section: Discussionmentioning
confidence: 95%
“…Very little is known about the pathophysiological relevance of the monoaminergic system in supraspinal structures related to the pain matrix. At supraspinal level, the 5HT and its main metabolite 5-HIAA levels are increased, both in the periaqueductal grey matter and in the trigeminal nucleus after a peripheral nerve axotomy, on the contrary the basal levels of 5HT decrease in the ventromedial thalamus in a neuropathic pain model induced by the ligature of the L5 and L6 spinal roots [6] [7]. In the medial prefrontal cortex, the extracellular levels of 5-hydroxyindoleacetic acid (5HIAA) and DOPAC (metabolite of dopamine) are decreased in the formalin test when there's a novel stimuli [8].…”
Section: Introductionmentioning
confidence: 92%
“…Is the monoaminergic descending inhibitory system activated or inhibited in the pathological pain state? It has been reported that peripheral neurectomy and polyarthritis are associated with marked increases in 5-HT, noradrenaline, and dopamine concentrations in the spinal cord (Colado et al 1994;Godefroy et al 1987), indicating the activation of monoaminergic descending system. Recently, Satoh and Omote (1996) found that the levels of monoamines involved 5-HT; noradrenaline increased bilaterally in the dorsal horn of the lumbar spinal cord in rats with peripheral mononeuropathy.…”
Section: Associative Learning and Pain? Why Stop There?mentioning
confidence: 99%